L'Offrande et le tribut. Histoire politique de la fiscalité en Judée hellénistique et romaine (200 a.C. - 135 p.C.), (Scripta Antiqua - 152). - Dąbrowa, Edward (Electrum, 2023)
The article "L'Offrande et le tribut. Histoire politique de la fiscalité en Judée hellénistique et romaine (200 a.C. - 135 p.C.)" by Michaël Girardin explores the history of taxation systems in ancient Israel, focusing on the periods of Hellenistic and Roman rule. Girardin's research delves into the complexities of taxation in Judea, highlighting the impact of political changes on fiscal policies. By examining the relationship between taxation, religious practices, and cultural identity, Girardin provides valuable insights into the historical context of taxation in ancient Israel. This comprehensive study sheds light on the intricate dynamics of taxation systems in Judea, offering a nuanced perspective on the intersection of politics, religion, and economics in the region.